BOARD HETEROGENEITY, AUDIT COMMITTEE GENDER AND CORPORATE TAX AGGRESSIVENESS OF LISTED CONSUMER GOODS FIRMS IN NIGERIA - Lawal, Lukman Ojedele; Lawal, Tajudeen; Abdulazeez, Daniya Adeiza (Kashere Journal of Management Sciences, 2024)
Aggressive tax planning are activities generally designed to reduce tax liability that includes tax evasion and legitimate saving of taxes. This study therefore aims to examine the impact of board heterogeneity on the tax aggressiveness, as well as the moderating effect of audit committee gender on the relationship between board heterogeneity and tax aggressiveness of listed consumer goods firms in Nigeria. Data were collected from one hundred and seventy financial years of firms in Nigeria from 2013-2022. The study analysed the data by means of descriptive statistics and correlation techniques. The regression results revealed that board nationality and board education have significant impact on tax aggressiveness. The finding of the study however, revealed that board composition has significant negative impact on tax aggressiveness. Similarly, the result from moderating model revealed that audit committee gender influenced the relationship between board heterogeneity and tax aggressiveness of the firms. The study therefore concludes that board heterogeneity is important in tax planning activities. The study recommends that the firms should maintain the number of foreign directors as well as maintaining the number of directors with training in accounting, finance and economics in order to continue to improving their tax planning activities. Similarly, the role of AC gender should be given ultimate attention when nominating AC members, since it improved the relationship between board heterogeneity and tax planning of consumer goods firms in Nigeria.